The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18806/tesl.v33i2.1235
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Beliefs About Corrective Feedback in the Language Classroom: Perspectives from Two International Contexts

Abstract: This study compared the beliefs college-level students hold about corrective feedback in different learning contexts: English as a second language (Canada, n = 197) and English as a foreign language (Russia, n = 224 Learner beliefs, defined as learners' metacognitive knowledge about learning (Wenden, 1999), are seen as "significant learner characteristics to take into account when explaining learning outcomes" (Dörnyei & Ryan, 2015, p. 187) because they shape and affect the way learners go about the task o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 74 publications
0
14
2
3
Order By: Relevance
“…The study revealed that many language learners stated that indirect feedback was more helpful. Other aspects to influence perception is from (Kartchava, 2016) on learners' beliefs about corrective feedback on perspectives from two international contexts. The study revealed that the respondents felt that feedback should be done and is preferable in L2 class.…”
Section: Related Workmentioning
confidence: 99%
“…The study revealed that many language learners stated that indirect feedback was more helpful. Other aspects to influence perception is from (Kartchava, 2016) on learners' beliefs about corrective feedback on perspectives from two international contexts. The study revealed that the respondents felt that feedback should be done and is preferable in L2 class.…”
Section: Related Workmentioning
confidence: 99%
“…Identification of the implementation of corrective feedback is as crucial as how students perceive it. There are some studies that explore the influence of perception on corrective feedback (Kartchava, 2016;Vyatkina, 2011;Jodaie, Farrokhi, & Zoghi, 2011;Rejab, Ismail, & Jamaludin, 2015), and learners' beliefs about corrective feedback perspectives from different contexts (Kartchava, 2016). Teachers' perception does not coincide with what students expect from their teachers in which Martinez Buffa (2016) captured teachers must assess students' expectations regarding written corrective feedback by knowing preferences that can be beneficial for both parties.…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that there are some studies on EFL learners' belief, like those about: grammar instruction and error correction conducted in Turkey (Incecay & Dollar, 2011); language learning (Bernat & Gvozdenko, 2005;Bernat & Lloyd, 2007; L Graham, 2006;(Truitt, 1995) Rifkin, 2000), aspects of language learning (A. Davis, 2008), oral corrective feedbacks (Yang, 2019), corrective feedback (Kartchava, 2016), relationship between self-efficacy belief and vocabulary learning strategy in Iranian EFL learners (Heidari et al, 2012), and that between gender, proficiency, learning strategies, and self-efficacy belief in Turkey (Yilmaz, 2010). This study is different since it tries to elicit the Indonesian EFL learners' beliefs in advantages of using songs in their EFL learning.…”
Section: Introductionmentioning
confidence: 99%